Konsentrasi beberapa ekstrak daun ketapang (Terminalia catappa L.) sebagai herbisida nabati pada pertumbuhan gulma rumput grinting (Cynodon dactylon (L.) Pers.) - Desiana Linda Nurhalina; Derek Kornelis Erari; Kati Syamsudin Kadang Tola; Yohanis Amos Mustamu (Fakultas Pertanian Universitas Papua, 2021)
The objectives of the study were to determine the inhibition of Terminalia catappa leaf extract on the growth of grinting grass weed (Cynodon dactylon (L.) Pers.) as well as determine at what concentration it could inhibit growth of grinting grass weed. The research method used in this study is an experimental method with observation techniques. The results of this study found that Terminalia catappa leaf extract can inhibit the growth of grinting grass weed (Cynodon dactylon (L.) Pers.). Furthermore, 20% of Terminalia catappa leaf extract was the most effective concentration in inhibiting grinting grass weed. Therefore, it can be used as an alternative to organic herbicides.